MORPHOLOGY AND SKELETAL DEVELOPMENT OF RAT (Rattus norvegicus) FETUS AFTER FED DIETS CONTAINING Calliandra calothyrsus LEAF DURING GESTATION PERIOD - Christiani, Ruth Ellisa; Setyawati, Iriani; Yulihastuti, Dwi Ariani (Jurnal Biologi Udayana, 2016)
This study aims to determine fetus morphology and skeleton development of rats after feddiet containingCalliandra leaf flour. This study used a completely randomized design with 16 pregnant rats that were dividedinto four treatment groups i.e. 0, 10, 17.5 and 25% of Calliandra leaf flour. The diets were given 20 g/rat/dayeach, twice a day, for 30 days (7 days of diet adaptation, 21 days of gestation period, and one day after birth).One day after the birth, all fetuses were separated from their mother for further preparation and analysis. Thedata were analyzed statistically by using SPSS 22 version. If they were distributed normally, the data would beanalyzed usingOneway ANOVA and Duncan Multiple Range Test (DMRT) to see the difference among the groups.Diets containing Calliandra leaf flour fed on pregnant rats decreased weight and length of fetuses and increasedfetus hemorrhage. However, it did not cause dead fetus or decreased the number of life fetuses. Diets containingCalliandra leaf flourfed to pregnant rats did not affect the ossification of vertebrae, costae and sternebrae. However,it inhibited ossification of metacarpus, metatarsus and vertebrae caudalis.
Keywords: Calliandra calothyrsus, fetal morphology, skeleton